Environmental component of the problem of increasing the durability of piston rings - Onikienko, V. (Харківський національний автомобільно-дорожній університет, 2023)
The work is devoted to the actual problem: Increasing the durability of piston rings using a modern method of surface treatment. Solving this problem with the help of traditional methods of chemical and thermal treatment does not give stable industrial results, therefore, the development of the technology of using modern methods and the methodology of their testing is an important urgent task.
Екологічна складова проблеми підвищення довговічності поршневих кілець
Keywords: piston; steel; durability; structure; 621.78:669.017